Genetic improvement of non-conventional Torulaspora delbrueckii for traditional sparkling winemaking by mixing for eventual hybridization with Saccharomyces cerevisiae - Martínez, Alberto; Zamora, Emiliano; Álvarez, María L.; Bautista-Gallego, Joaquín; Ramírez, Manuel (Frontiers in Microbiology, 2022)
Non-conventional yeasts such as Torulaspora delbrueckii (Td) have been proposed for sparkling wine making. Unfortunately, this yeast has poor efficiency in completing wine fermentation as compared to Saccharomyces cerevisiae (Sc). New mutants with increased resistance to SO2, ethanol, and high CO2 pressure were previously isolated from spore clones of Td. Although these mutants showed improved capability for base wine fermentation, there is still room for genetic improvement of Td yeasts until the fermentative capacity of Sc is achieved. As an alternative approach, hybridization of Td with Sc was assayed in this study. The new hybridized yeasts (Sc-hybridized Td) showed an intermediate phenotype between both parent yeasts for some relevant biotechnological properties, such as resistance to SO2, ethanol, copper, high CO2 pressure, and high temperature, as well as flocculation potential. These properties varied depending on the specific Sc-hybridized Td clone. Several hybridized clones showed improved capability for base wine fermentation as compared to the Td parent strain, approaching the fermentation capability of the Sc parent strain. The organoleptic quality of sparkling wine was also improved by using some hybridized clones, and this improved quality coincided with an increased amount of acetate and ethyl esters. The genetic stability of some Sc-hybridized Td clones was good enough for commercial yeast production and winery applications.